Pengaruh Perbandingan Konsentrasi Tempe dan Puree Daging Buah Pala terhadap Mutu Nugget Selama Penyimpanan - Lawalata, Vita N; Tetelepta, Gilian (AGRITEKNO: Jurnal Teknologi Pertanian, 2025)
This study aimed to determine the appropriate ratio of tempe and nutmeg puree concentration for producing good quality of tempeh nuggets during storage. A completely randomized design with one factor and four treatment levels was used, consisting of tempeh to nutmeg puree ratios of 60%:0%, 58,5%:1.5%, 57%: 3%, and 55.5%:4.5%. The observed variables included chemical characteristics (moisture content, ash content, soluble protein, fat content, and peroxide value), total microbial count, and organoleptic properties. The ratio of 55.5% tempeh to 4.5% nutmeg puree produced the best nuggets based on chemical and microbial characteristics, with moisture content (51.6%), ash content (3.35%), soluble protein content (2.52%,), fat content (7.7%), peroxide value (0.26 mg O2/100g), and total microbial count (4.1×102 CFU/g). Meanwhile, based on organoleptic evaluation, the color was liked (3.12), the aroma was slightly liked (2.52), the taste was close to liked (2.88), and the overall acceptability was also close to liked (2.86)